Effect of Age and Body Size on the Wrist's Viscoelasticity in Healthy Participants From 3 to 90 Years Old and Reliability Assessment - Nguyen, Anh Phong; Herman, Benoit; Mahaudens, Philippe; Everard, Gauthier; Libert, Thibaut; Detrembleur, Christine (Frontiers in Sports and Active Living, 2020)
Excessive or insufficient levels of passive musculoarticular stiffness (PMAS) can lead to joint impairment or instability. Quantifying the PMAS may provide a better understanding of neurological or musculoskeletal disorders. Aims of present study were multiple: first, to assess the reliability of quantifying PMAS and to collect normative data on the wrist in healthy participants, and second, to assess the effect of age and body size on PMAS. For this purpose, a total of 458 participants from 3 to 90-year-old were analyzed with an Electromechanical Oscillation Device (EOD). Passive sinusoidal movements were induced in a flexion/extension pattern in the participants’ wrists enabling an objective measurement of elastic stiffness (EL) and viscous stiffness (VI). Both the dominant and non-dominant wrists were assessed. Two-way repeated measures ANOVA revealed a sex differentiation from puberty (12-18-year-old) and an increase of EL and VI from childhood to adulthood and a decrease of stiffness at old age. EL and VI values were associated to body size characteristics and age. After body size normalization, EL was no longer influenced by the variables measured. On the other hand, VI remained moderately influenced by age and body size. The current study was able to provide normative data of PMAS in the wrist of healthy participants.